2015
DOI: 10.4236/fns.2015.615145
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional and Anti-Nutrient Composition of Three Kola Nuts (<i> Cola nitida, Cola acuminata </i> and <i> Garcinia kola </i>) Produced in Benin

Abstract: Kola nuts were regularly chewed by West Africans and Beninese in particularly. The aim of this study was to investigate nutritional and anti-nutrient content of three Benin's kola nuts (Cola nitida, Cola acuminata and Garcinia kola). Proximate composition of the three species of kola nuts was assessed using standard analytical AOAC methods. Phenolics and flavonoids contents were determined by Folin-Ciocalteu and aluminum trichloride methods, respectively. Mineral composition was determined by Atomic Absorption… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 37 publications
1
24
0
Order By: Relevance
“…In addition, bioflavonoids are known as plant chemicals with estrogenic activity, and studies have shown that estrogen promotes growth in common carp (Kocour et al 2005). As aforementioned above, phytochemical studies of Garcinia kola seeds have revealed relatively low levels of antinutritional compounds such as tannin, oxalate, phytate, and trypsin inhibitor (Omeh et al 2014, Dah-Nouvlessounon et al 2015. However, the increase in dietary supplementation of G. kola is naturally followed by that of the above-mentioned anti-nutritional components.…”
Section: Discussionmentioning
confidence: 96%
“…In addition, bioflavonoids are known as plant chemicals with estrogenic activity, and studies have shown that estrogen promotes growth in common carp (Kocour et al 2005). As aforementioned above, phytochemical studies of Garcinia kola seeds have revealed relatively low levels of antinutritional compounds such as tannin, oxalate, phytate, and trypsin inhibitor (Omeh et al 2014, Dah-Nouvlessounon et al 2015. However, the increase in dietary supplementation of G. kola is naturally followed by that of the above-mentioned anti-nutritional components.…”
Section: Discussionmentioning
confidence: 96%
“…The aspartic acid helps to promote a robust body metabolism and it is used to treat depression and fatigue [12]. The kola industry offers a lot of employment and income opportunities to people involved in the harvesting, processing, packaging and transportation of nuts [13][14][15]. The crop has socio-cultural importance in Africa especially during traditional rites [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, the Food and Agricultural Organization of the United Nations (FAO) is currently promoting the conservation and sustainable use of biodiversity for nutrition and agriculture as a means to increase dietary diversity [7,8,9]. However, the main problem relating to the full exploitation of some of these wild fruits is the presence of some antinutrients, which have the potential to reduce especially protein and starch digestibility and mineral bioavailability [10,11,12].…”
Section: Introductionmentioning
confidence: 99%